Screening Mediterranean shrubs selected by browsing goats against gastrointestinal strongyles - Padre, Ludovina (2021)
Ethanolic extracts from the main species selected by browsing Charnequeira goats on Mediterranean vegetation were assayed for a rapid screening of their anthelmintic potential against gastrointestinal (GI) strongyles. Shrubs selected included Olea europeae var. sylvestris (OS), Quercus coccifera (QC), Pistacia lentiscus, Rhamnus alaternus and Rhamnus lycioides (RL). Forage species included Cichorium intybus (CI) and Hedysarum coronarium (HC). Extract concentrations were chosen taking as reference the fecal total phenolics content (TP) from those goats after a five-month browsing period (8.4 mg GAE/g DM). A quantitative coproculture method was adapted using faeces obtained from naturally infected goats, not dewormed or having access to browse (reference group); larvae culture was performed in triplicate for three different TP concentrations (25, 10 and 5 mg GAE/g DM) against a distilled water control, for a 7-day incubation period at 27 °C. The number of larvae developed was counted differentiating total and live larvae per gram of faeces (LDPG). The efficacy of each extract and concentration, as percentage of reduction in LDPG against control, was determined. Data was log transformed and submitted to analysis of variance. Means were compared by Tukey test at 5% significance level.A reduction in LDPG was observed in all extracts being significant (P<0.05) for the highest concentration. The extracts’ efficacy over exogenous forms showed not only a reduction of total LDPG but, for some, also a high level of larvae mortality, resulting in reduction of live infective larvae (L3). These results indicate that some extracts, besides their ovicidal activity, have also larvicidal potential. Extracts efficacy for total LDPG was higher for QC (82%), OS (80%), HC and RL (76%) and CI (69%). Reduction of live L3 was higher for OS (90%) and HC (80%). Results obtained on these extracts potential in reducing exogenous forms, namely L3 forms of GI strongyles, is an important aspect in the control of these parasitic populations, as it results in lower pasture contamination and consequently a lower rate of reinfection of the animals. Funding obtained from project VegMedCabras – ALT20-03-0145-FEDER-000009